Desain Perancangan Alat Guna Pemberi Informasi Kebocoran Gas Metode Fuzzy Melalui SMS Gatway Berbasis Arduino Uno - ahmad fauzi; Andry Maulana; Rian Septian Anwar (JURNAL TEKNIK KOMPUTER, 2020)
Abstract  - Natural resources that are beneficial to human life are very much available in this earth, one of the processing of natural resources in the form of gas that is LPG Gas. The role of LPG gas at this time is very important for human life both in the household and in industry. Actual explosion or gas leak can be avoided with a security system and early warning. In this Final Project the authors do the design and manufacture of a gas detector sensor using Arduino Uno MQ-5 sensor. There will be a warning via a short message when the gas condition is detected by the sensor, this tool will send a message to the user's mobile phone that there is a gas leak. Based on the test results, this tool is able to detect LPG gas leak in a room, but it is also capable of sending an sms containing gas leak warning to the user of the tool. As a warning there has been a gas leak in the room or home of the gas user. With the creation of this tool, LPG tube monitoring process can be done easily and safely. And this tool can be developed again using internet-based notifications.